Application of Half-Transected and Self-Pulling Esophagojejunostomy in Total Laparoscopic Gastrectomy for Gastric Cancer: A Safe and Feasible Technique - Hongtao Wan; Jianyong Xiong; Yanglin Chen; Haiyun Wei; Ren Tang; Chao Chen; Qing Sun; Jing Xu; Bo Yi (Canadian Journal of Gastroenterology and Hepatology)
Objective. This study introduces a technique for esophagojejunostomy with half transected and self-pulling (HTSP) and evaluates the safety, feasibility, and clinical results of this technique in totally laparoscopic total gastrectomy (TLTG). Materials and Methods. From May 2019 to March 2021, 42 patients (HTSP group) who underwent HTSP-TLTG surgery in the Department of Abdominal Tumor Surgery of Jiangxi Cancer Hospital were included in this study. The control group consisted of 50 patients undergoing conventional TLTG surgery (conventional anastomosis group) performed by the same surgical team from March 2018 to March 2020. The clinical data of the two groups were retrospectively analyzed and compared. Results. The mean operation time of the HTSP-TLTG surgery was 166.7 ± 13.1 minutes and the anastomosis time was 20.8 ± 2.0 minutes, which were significantly shorter than those of traditional TLTG (P<0.05). There were no significant differences between the two groups in blood loss, time to first exhaust, postoperative hospital stay, and incidence of surgery-related complications. Conclusion. HTSP is a safe and feasible way of endoscopic esophagojejunal anastomosis, which requires a relatively low suture technique under endoscopy, and is suitable for promotion.